PERAN PSYCHOLOGICAL CAPITAL PADA ORANGTUA TUNGGAL (IBU) DALAM MENDIDIK ANAK USIA SEKOLAH - Khotmi, Nurmaulia (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
Psychological capital is the psychological capital possessed by every person, and it is the development of positive psychological conditions in every person. This psychological capital consists of hope, optimism, resilience, and efficacy, abbreviated as HORE. This study examines the experiences of single parents, namely mothers, in the education of children under the age of 18 or school-age children without the accompaniment of a husband. Single parents (mothers) are women who were once married but have been widowed or divorced from their husbands. The purpose of this study is to understand the role of psychological capital possessed by single parents (mothers) in educating their children without the material or moral support of their husbands. The method used is qualitative with a phenomenological approach. Data collection was conducted through in-depth interviews with several single mothers (mothers) by the researcher. The research findings indicate that these four psychological capital factors play a significant role in educating or caring for children amid economic limitations and the absence of moral support from a partner.